Caracterización del rol de la mujer en la gerencia de proyectos en Colombia (2015)
This report includes the fundamental aspects of the work carried out based on what was proposed in the initial proposal and in the management plan for the degree work, and the development throughout the execution period. The recommendations received during the class sessions of the subjects prior to the completion of the work were followed. As a first step, a literature review was carried out on the competencies required for a project manager to perform satisfactorily, based on standards proposed by organizations such as the Project Management Institute, PMI; the International Project Management Association (IPMA), the Association for Project Management (APM) and the Australion Institute of Project Management (A / PM). The inclusion of the ISO standard was considered, but it was found that its proposal is based on that of the PMI. The information of the standards was complemented with the results of different research on skills and competencies and on the participation of women in managerial roles, particularly in project management.